Use of different options of anti-inflammatory therapy in patients with severe COVID-19 - Skoryk, Vita (ScienceRise: Medical Science, 2021)
The aim of the study. To compare the effectiveness of methylprednisolone, dexamethasone and tocilizumab in patients with severe coronavirus disease. Identify the most appropriate treatment option. Materials and methods. Patients of group 1 (n=20) received for anti-inflammatory purposes tocilizumab at a dose of 600–800 mg. Patients in group 2 (n=82) received pulse therapy with methylprednisolone. Patients in group 3 (n=20) received dexamethasone 6 mg / day. Data are presented as M [25–75]. Statistical analysis of the results was performed using the program "Statistica 10". Significance of differences in indicators was assessed using the nonparametric Wilcoxon test. The results were considered reliable at values of p <0.05. Results. The severe course of coronavirus disease with the development of cytokine storm and respiratory distress syndrome is characterized by an increase in markers of inflammation: in group 1 the median CRP was 89.2 g / l, in group 2 – 64.2 g / l, and in 3 – 76.2 g / l, and did not differ significantly between groups (p> 0.05). The level of IL-6 in group 1 was 61.8 pg / ml, in group 2 – 64.6 pg / ml, and in group 3 – 46.5 pg / ml without significant differences between groups (p> 0.05). The level of ferritin in all groups exceeded normal values. Conclusions The most favourable result was obtained when using methylprednisolone: it was possible to reduce the mortality rate to 59.8 %. The relative risk of developing VTE was significantly higher in groups 1 and 3 (RR12 6.8 [2.7–16.8] p12 <0.0001, RR23 0.15 [0.06–0.35] p23 <0.0001), which gives grounds to confirm the presence of anticoagulant activity in methylprednisolone